2016
DOI: 10.15244/pjoes/60315
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Bioanalysis: an Effective Tool for Data Collection of Environmental Conditions and Processes

Abstract: Reliable information that allows us to estimate the state of the environment and to forecast changes in the ecosystem are constantly required. Increasing environmental consciousness and dynamic development of analytical techniques are the main reasons for determining the wide range of pollutants occurring at very low concentrations in complex matrix samples. The presence and concentration of many of those pollutants in the environment are not yet subjected to legal regulations, so development of new methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…It was observed that water hardness had an adverse effect on washing and rubbing fastness when fabric was dyed with both turmeric and eucalyptus extracts. Therefore, based on this study, the use of mordanting/sequestering agent is suggested to enhance the dye uptake and previous studies also revealed a similar trend that mordanting/sequestering can be used to enhance the color strength and color properties [27][28][29][30][31][32][33][34][35][36], and in view of current environmental pollution [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the natural sources should be preferred to avoid a negative impact on the environment.…”
Section: Color Propertiessupporting
confidence: 63%
“…It was observed that water hardness had an adverse effect on washing and rubbing fastness when fabric was dyed with both turmeric and eucalyptus extracts. Therefore, based on this study, the use of mordanting/sequestering agent is suggested to enhance the dye uptake and previous studies also revealed a similar trend that mordanting/sequestering can be used to enhance the color strength and color properties [27][28][29][30][31][32][33][34][35][36], and in view of current environmental pollution [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the natural sources should be preferred to avoid a negative impact on the environment.…”
Section: Color Propertiessupporting
confidence: 63%
“…Uddin and his co-workers also performed scientific justification of the anti-inflammatory, anti-nociceptive, and antipyretic effects of V. grandiflorum with respect to its chemical composition. Viburnum species are also used for treating different diseases such as diarrhoea, rheumatoid arthritis, tumefaction, anti-diabetic, antioxidant and anti-bacterial [13][14]. The present study was undertaken to investigate the phytochemical composition and antioxidant and antimicrobial properties of the stem parts of V. grandiflorum.…”
Section: Introductionmentioning
confidence: 99%
“…Cynodon dactylon occurs on almost all soil types Ahmad et al [39] since the cities are an important habitat for an array of physical, economic, social, political, and cultural capitals. Therefore, there is a need to think carefully about the nature, operation, and forms of cities -particularly in respect to the challenging issue of sustainability and the current scenario of environmental issues [45][46][47][48][49][50][51][52][53][54][55] also demand such practices. Urbanization is a danger to climate change and resultantly, biodiversity and natural habitat loss, air pollution exceeding safe limits, and urban flooding may change [56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Urbanization Planning In Zonementioning
confidence: 99%